2003
DOI: 10.1088/0305-4470/36/35/302
|View full text |Cite
|
Sign up to set email alerts
|

The strain of CuO2lattice: the second variable for the phase diagram of cuprate perovskites

Abstract: We show the key role of the elastic local strain (or micro-strain) ε of the CuO 2 lattice in the phase diagram of cuprate superconductors. The superconducting critical temperature T c (δ, ε) is shown to be a function of two variables, the doping δ and the microstrain ε.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
93
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 54 publications
7
93
0
Order By: Relevance
“…While present in all cuprates [19][20][21][22][23], it is not well understood so that its consequences for the various experimental probes are not clear. In NMR, one finds various degrees of line broadening in the various cuprates (see e.g., [24]) typically caused by concomitant charge and spin density variations [25].…”
Section: Introductionmentioning
confidence: 99%
“…While present in all cuprates [19][20][21][22][23], it is not well understood so that its consequences for the various experimental probes are not clear. In NMR, one finds various degrees of line broadening in the various cuprates (see e.g., [24]) typically caused by concomitant charge and spin density variations [25].…”
Section: Introductionmentioning
confidence: 99%
“…For many years the dominant theories of HTS have considered a stoichiometric CuO 2 layer and have neglected the key role of lattice effects (16,17), even if the ½CuO 2 ∞ layers are intercalated by a variety of defective oxide AO layers (A=La, Ba, Sr, Ca, Y, Hg or Rare earths) with a large tolerance factor (18) or misfit strain (19,20) and a large number of oxygen interstitials or defects. The lattice misfit induces tilting and corrugation of the ½CuO 2 ∞ layers and structural phase transitions going from I4∕mmm (high temperature tetragonal), Bmab, Pccn, and Fmmm (low temperature orthorhombic, LTO) to P4 2 ∕ncm (low temperature tetragonal) in systems like La 2 CuO 4 (21).…”
mentioning
confidence: 99%
“…We note that the above considerations have focused on average bond distances and bond angles. There exists ample evidence from local bulk probes that the cuprates exhibit significant compound-specific local deviations from the average crystal structure [41,42], and that the charge distributions in both LSCO [43] and Hg1201 [44] vary on the nanoscale. Based on modeling the disorder in the interstitial layers, it was concluded that the hole mean free path and the screening of the Coulomb repulsion in Hg1201 are substantially larger than in LSCO, hence contributing to the higher T c [39].…”
mentioning
confidence: 99%